Destabilizing the Global Monetary System : Germany's Adoption of the Gold Standard in the Early 1870s - Wiegand, Johannes (IMF Working Papers; Working Paper ;, 2019)
In 1871-73, newly unified Germany adopted the gold standard, replacing the silver-based currencies that had been prevalent in most German states until then. The reform sparked a series of steps in other countries that ultimately ended global bimetallism, id est, a near-universal fixed exchange rate system in which (mostly) France stabilized the exchange value between gold and silver currencies. As a result, silver currencies depreciated sharply, and severe deflation ensued in the gold block. Why did Germany switch to gold and set the train of destructive events in motion? Both a review of the contemporaneous debate and statistical evidence suggest that it acted preemptively: the Australian and Californian gold discoveries of around 1850 had greatly increased the global supply of gold. By the mid-1860s, gold threatened to crowd out silver money in France, which would have severed the link between gold and silver currencies. Without reform, Germany would thus have risked exclusion from the fixed exchange rate system that tied together the major industrial economies. Reform required French accommodation, however. Victory in the Franco-Prussian war of 1870/71 allowed Germany to force accommodation, but only until France settled the war indemnity and regained sovereignty in late 1873. In this situation, switching to gold was superior to adopting bimetallism, as it prevented France from derailing Germany's reform ex-post.